1982
DOI: 10.1039/f19827803537
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of the decomposition mechanism of platinum and palladium tetrammine faujasite X

Abstract: The decomposition of platinum and palladium tetrammine faujasite X has been studied by temperatureprogrammed desorption (t .p.d.) spectroscopy, differential thermal analysis and derivative thermogravimetry . Well resolved t.p.d. spectra allowed the deduction of a detailed mechanism with respect to autoreduction, ammonia evolution and the reaction of ammonia with acid sites. Characteristic differences observed between the palladium and platinum samples are related to the lower stability of the palladium tetramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 0 publications
3
17
1
Order By: Relevance
“…Our observation of PtO decomposition over the temperature range 773 to 873 K is consistent with decomposition temperatures of PtO published elsewhere [24,34,94]. The dramatically reduced intensity of the PtO peak in Figure 4.1 (d) [63). The massive migration of platinum to the exterior of the zeolite crystallite during reduction of the undecomposed metal-tetraammine complex [84] is consistent with the formation of a mobile metal hydride species, Pt(NH 3 )2H 2 , as suggested by Dalla-Betta and Boudart [10].…”
Section: Raman Spectroscopy Experimentssupporting
confidence: 79%
See 1 more Smart Citation
“…Our observation of PtO decomposition over the temperature range 773 to 873 K is consistent with decomposition temperatures of PtO published elsewhere [24,34,94]. The dramatically reduced intensity of the PtO peak in Figure 4.1 (d) [63). The massive migration of platinum to the exterior of the zeolite crystallite during reduction of the undecomposed metal-tetraammine complex [84] is consistent with the formation of a mobile metal hydride species, Pt(NH 3 )2H 2 , as suggested by Dalla-Betta and Boudart [10].…”
Section: Raman Spectroscopy Experimentssupporting
confidence: 79%
“…Accordingly, the mottled crystallite backgrounds in Figure 3.2 (b) 129 Xe adsorbed on Y zeolites exchanged with a large fraction of divalent alkaline earth cations [39]. Indeed, the chemical shift behavior we observe for xenon adsorbed on dehydrated Pt(NH 3 );+ -NaY is consistent with previously reported data for Ba2+ -NaY Under more severe calcination treatments at 573 K and 673 K, the catalyst mate- rial changes color from white to dark gray as the metal complex decomposes (50,63]. (24,34] show that nearly all of the platinum is located in the supercages and is, therefore, accessible to the molecular xenon probe.…”
supporting
confidence: 80%
“…); it was found that a low concentration of [Pt(NH 3 ) 4 ] 2+ at room temperature is a good condition for the exchange (5 4 ] 2+ in zeolites were examined in many studies, because they can be of great influence on the location and size of the metal particles formed in the subsequent reduction. The studies in which both Pt and Pd were examined showed that both metals behave similarly in the pretreatment process (2,5,6). The differences between the metals that were reported are the greater tendency to autoreduction of [Pt(NH 3 ) 4 ] 2+ in zeolites (5) and the lower stability of [Pd(NH 3 ) 4 ] 2+ in zeolite X (6).…”
Section: Introductionmentioning
confidence: 96%
“…The studies in which both Pt and Pd were examined showed that both metals behave similarly in the pretreatment process (2,5,6). The differences between the metals that were reported are the greater tendency to autoreduction of [Pt(NH 3 ) 4 ] 2+ in zeolites (5) and the lower stability of [Pd(NH 3 ) 4 ] 2+ in zeolite X (6). Therefore, also studies are discussed here that concern [Pd(NH 3 ) 4 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation